Characteristics of vegetation in the gumuk ecosystem in Jember District, East Java, Indonesia - WIWIN MAISYAROH; LUCHMAN HAKIM; SUDARTO SUDARTO; JATI BATORO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Maisyaroh W, Hakim L, Sudarto, Batoro J. 2023. Characteristics of vegetation in the gumuk ecosystem in Jember District, East Java, Indonesia. Biodiversitas 24: 1264-1271. Gumuk is a unique Jember district landscape with high ecological value. Currently, gumuk mining is increasing. This study aims to look at the characteristics of the vegetation in the gumuk ecosystem based on a variety of landuses (mixed garden, sand mining, and stone mining). The field survey was carried out at Ledokombo Sub-district, Jember District, East Java, from January to March 2021. First, the distribution of gumuk was identified using GIS, referring to the Van Zuidam landform classification. Then, a vegetation survey was conducted to describe the vegetation structure of the gumuk ecosystem, found 136 gumuk. Gumuk can be classified as gumuk with mixed garden, gumuk for stone mining, and gumuk for sand mining. A total of 202 species (65 families) grow in the gumuk ecosystem. Seedlings had the highest number of species, dominated by Asteraceae and Poaceae, while Malvaceae dominated saplings, poles, and trees. The Gumuk with the highest number of species for all habitus was found at gumuk with mixed gardening category, followed by gumuk with stone mining activity and gumuk for sand mining. At gumuk, mixed garden (H' 4) and stone mining (H' 3.47) had a high diversity of vegetation for seedlings, with the species having the highest IVI being Digitaria sanguinalis. At gumuk sand mining, it also has a high diversity of vegetation (H' 3.06) for seedlings, with the species having the highest IVI being Commelina erecta.